Assistive robotics as therapy for autistic children - Tanevska, Ana; Ackovska, Nevena; Kirandziska, Vesna (My University, 2016)
Assistive technology encompasses in its domain all rehabilitative tech, be it software or hardware, that works on improving quality of life for physically and mentally disabled people. Unlike creating assistive devices for people with physical disabilities, developing treatments for people with cognitive impairments is a very difficult task, due to the fact that cognitive disorders manifest differently from one group of people to another. One such specific group are children with Autism Spectrum Disorder (ASD). ASD is a condition that affects normal socio-emotional development in early childhood and causes difficulties with learning. One kind of treatment that has proven itself as particularly effective for young autistic children is robotassisted therapy (RAT), which involves a robotic element – this can be robotic toys, robotic platforms, humanoid robots – with the purpose of making the learning process easier for these children. This paper elaborates on several different approaches for implementing robots in autism therapy, gives an overview on several RAT studies done in the world, and presents our work done in implementing a NAO humanoid robot in a research experiment with children on the autism spectrum.
Keywords: autism spectrum disorder, human-robot interaction, NAO humanoid robot, robot-assisted therapy, assistive robotics